Determinação da posição da extremidade distal do cateter venoso umbilical: uma comparação entre ecocardiografia e radiografia anteroposterior de tórax - Adriana Furletti Machado Guimarães (2015)
Objectives: To evaluate the accuracy of the simultaneous analysis of three radiographic anatomical landmarks - diaphragm, cardiac silhouette and vertebral bodies, in determining the distal end of umbilical venous catheter (UVC) position using echocardiography as a reference standard; to evaluate the vertebral levels performance alone to predict the position of the UVC; to evaluate the relationship between birth weight and gestational age with catheter positioning; to evaluate the concordance of the analyses of the chest radiograph between a radiologist and a pediatrician and compare the variations of Dunn technique with the incidence of repositioning. Methods: Cross-sectional study, observational, with prospective inclusion of data of neonates subject to the insertion of UVC as part of clinical care. The position of the distal end of the CVU, determined by simultaneous analysis of three radiographic anatomical landmarks, was compared with the anatomical position obtained by echocardiography and the sensitivity, specificity, positive predictive value, negative predictive value and accuracy were calculated. A ROC curve (Receiver operating characteristic) was constructed with the objective of evaluating the vertebral levels performance in predicting the position of the UVC. A comparative analysis was made between the positioning of the catheter and the variables: gestational age and birth weight. The interobserver agreement was assessed by Kappa index. The measures of the shoulder-navel distance in a straight vertical line and in a straight diagonal line were compared with the repositioning of the CVU. Results: The accuracy of the chest radiography to detect catheter in the target area was 67.28%. The evaluation of the vertebral bodys performance to predict the position of the catheter showed a low method's ability to discriminate between well and malpositioned catheters (area under the ROC curve 0.66). Lower average gestational age and lower average birth weight were associated with higher incidence of poor positioning of the CVU (p <0.01). The Kappa index of interobserver agreement (pediatrician and radiologist) in determining the distal end of the CVU, when analyzing the anteroposterior radiograph of the chest, ranged from reasonable to good (0.52). The measure of the shoulder-navel distance in a straight diagonal line was associated with an increased need for repositioning the CVU (p <0.01). Conclusion: The isolated anteroposterior chest radiography, even while simultaneously analyzing cardiac silhouette, diaphragm and vertebral bodies, is not able to set the safety position of the distal end of UVC. Echocardiography allows direct visualization of the catheter tip in relation to the vascular structures and should be considered as reference standard to locate the UVC.